Production process of hardware elastic sheet with stable contact performance
By optimizing material selection and process flow, including the use of copper alloy and specific elements, step-by-step smelting and specific heat treatment, the problem of degraded contact performance of hardware shrapnel is solved, significantly improving its corrosion resistance and service life.
Patent Information
- Application Number
- CN202411584113.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-07
AI Technical Summary
After long-term use of existing hardware shrapnel, due to material fatigue, surface wear or oxidation, the contact performance of existing hardware shrapnel declines, resulting in unstable electrical connections, affecting the reliability and service life of the product.
By optimizing material selection, copper alloy is used as the raw material for hardware shrapnel, a specific proportion of metal elements Be, P, Sn, and Zn are introduced, and the raw materials are added in step by step for smelting, specific heat treatment and surface treatment steps to improve the resistance of hardware shrapnel Corrosiveness and contact properties.
After millions of mechanical cycle tests, the hardware shrapnel can still maintain excellent contact performance and stable electrical characteristics, significantly improving the reliability and service life of the product.
Smart Images

Figure BDA0005123886290000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hardware processing, and in particular relates to a production process of a hardware spring piece with stable contact performance. Background Art
[0002] In the field of metal spring technology, the stability and durability of contact performance have always been important technical indicators. Metal springs are widely used in a variety of products such as mobile phone cards, mobile phone antennas, membrane switches, contact switches, PCB boards, FPC boards, medical devices, headphone audio jacks, connectors, micro motors, sensors, relay switches, digital 3C products, and automotive instrument touch switches. However, after long-term use, the metal springs in the prior art often have the problem of reduced contact performance due to material fatigue, surface wear or oxidation, resulting in unstable electrical connections and affecting the reliability and service life of the product.
[0003] Although the traditional production process of hardware shrapnel can meet basic manufacturing needs to a certain extent, it still has shortcomings in improving the corrosion resistance and contact performance of the shrapnel. For example, some production processes lack fine control in material selection, stamping, surface treatment and other links, which makes the shrapnel prone to deformation, wear or corrosion after long-term use, thus affecting its contact performance.
[0004] In order to solve the above problems, the present invention proposes a production process of a hardware spring piece with stable contact performance, aiming to improve the corrosion resistance and contact performance of the hardware spring piece. Summary of the invention
[0005] The purpose of the present invention is to provide a production process for a hardware spring piece with stable contact performance. By optimizing material selection, strengthening surface treatment and other measures, the corrosion resistance and contact performance of the hardware spring piece are improved. After millions of mechanical cycle tests, the hardware spring piece can still maintain excellent contact performance and stable electrical characteristics, thereby significantly improving the reliability and service life of the product.
[0006] A production process of a metal spring with stable contact performance comprises the following steps:
[0007] S1, casting the raw materials to obtain a preliminary sample;
[0008] S2. After the initial sample is subjected to heat treatment and surface treatment in sequence, it is subjected to precision testing and is considered qualified.
[0009] Preferably, the raw material is any one of stainless steel, copper and copper alloy.
[0010] Preferably, the copper alloy comprises, by weight percentage, Be: 0.5% to 3%, P: 0.05% to 0.2%, Sn: 1% to 3%, Zn: 2% to 4%, and the remainder is Cu.
[0011] The inventors found that by selecting copper alloy as the raw material of the hardware shrapnel and introducing a specific proportion of metal elements Be, P, Sn, and Zn, the corrosion resistance of the hardware shrapnel can be improved while its mechanical properties can be improved. This may be because on the one hand, phosphorus can react with other impurities in copper to form high-melting-point compounds, thereby improving the thermal stability and corrosion resistance of the copper alloy; while zinc can form a dense oxide film on the surface of the copper alloy to prevent the erosion of corrosive media. The synergistic effect of these elements makes the hardware shrapnel have excellent corrosion resistance. On the other hand, the addition of beryllium, tin and zinc can significantly improve the strength and hardness of the copper alloy, while phosphorus can improve the fluidity of the copper melt, which helps to improve the casting performance and shape stability of the copper alloy. The synergistic effect of these elements makes the hardware shrapnel have excellent mechanical properties and can withstand large external forces and deformation without damage. In addition, copper, as the main component of copper alloy, has good conductivity. Although the addition of beryllium, phosphorus, tin and zinc will affect the electrical properties of copper, such as contact resistance, to a certain extent, when their content is controlled within an appropriate range, the effect on the electrical properties of the copper alloy is small, so that the hardware springs can maintain good electrical properties while having high reliability and long service life, and can work stably in electronic equipment.
[0012] The specific steps of the casting molding are:
[0013] A1. Weigh copper ingots, tin ingots, zinc ingots, and Cu-P and Cu-Be master alloys according to the weight percentages of the elements of the raw materials;
[0014] A2, putting copper ingots, tin ingots, zinc ingots, and Cu-P and Cu-Be master alloys into an induction melting furnace, heating, stirring and keeping warm to obtain a melt;
[0015] A3, refining, degassing, and stirring the melt obtained in step A2, and then standing and keeping warm for 8 to 12 minutes;
[0016] A4. The melt obtained in step A3 is transferred to a preheated metal spring-shaped mold for cold stamping to obtain a preliminary sample.
[0017] Preferably, the weight percentages of the metals in the Cu-P and Cu-Be master alloys are Cu-10P and Cu-2.0Be, respectively.
[0018] Preferably, the specific operation steps of step A2 are: preheating the smelting furnace to 400-500°C, adding copper ingots, heating to 1100-1150°C, keeping warm for 15-25 minutes after complete melting, cooling to 1000-1100°C, adding tin ingots and zinc ingots, keeping warm for 15-25 minutes after complete melting, cooling to 900-1000°C, adding Cu-P master alloy, keeping warm for 15-25 minutes after complete melting, heating to 1100-1200°C, adding Cu-Be master alloy, keeping warm for 15-25 minutes after complete melting, and obtaining a melt.
[0019] In some preferred schemes, the various properties of the hardware shrapnel can be further improved by adding raw materials step by step for smelting and controlling the temperature. This may be because the melting points of the elements and the roles they play in the system are different. During the heating process, metal raw materials such as copper ingots, tin ingots and zinc ingots gradually melt and are evenly mixed in the smelting furnace. During this process, the temperature and composition of the melt change, but the main physical change occurs; after adding Cu-P master alloy and Cu-Be master alloy, the elements in these alloys will react chemically with the elements such as copper, tin, and zinc in the melt to form new compounds or solid solutions. These chemical reactions promote the alloying process, making the composition and organization of the melt more complex and stable. By adding smelting step by step, not only can the uniform distribution of the elements in the hardware shrapnel be ensured, the formation of segregation and inclusions can be reduced, but also the microstructure morphology of the hardware shrapnel can be optimized, thereby improving its mechanical properties, corrosion resistance and electrical properties.
[0020] Preferably, the specific conditions for the cold stamping forming are: the punch tonnage is 90 to 110 tons, and the stamping speed is 30 to 50 times / min.
[0021] The specific steps of the heat treatment are:
[0022] B1. Heat the initial sample to 150-250℃ and keep it warm for 5-10min, heat it to 380-500℃ and keep it warm for 5-10min, heat it to 600-700℃ and keep it warm for 30-60min, and cool it to room temperature with the furnace;
[0023] B2, heat the B1 sample to 800-900°C, keep it warm for 30-60 minutes, and quickly cool it to room temperature;
[0024] B3. Heat the B2 sample to 300-450°C, keep it warm for 2-4 hours, and air cool it to room temperature.
[0025] The inventors found that by a specific heat treatment step, internal stress can be eliminated and various properties of the hardware shrapnel can be improved. This may be because the step-by-step temperature increase treatment in step B1 can effectively release the internal stress in the sample, reduce the thermal stress caused by temperature changes, and perform preliminary heat preservation at a lower temperature, which helps the elements in the alloy to further diffuse and evenly distribute, reduce component segregation, ensure the stability and uniformity of the sample during high temperature treatment, and improve its mechanical properties. The high temperature insulation and rapid cooling in step B2 further promote the refinement and homogenization of the organization, and enhance the strength and hardness of the hardware shrapnel. The residual stress and dislocation generated during the rapid cooling process are eliminated or reduced during the tempering process in step B3, so that the toughness and elasticity of the hardware shrapnel are improved. Through a reasonable heat treatment process, the toughness and plasticity of the hardware shrapnel can be improved while ensuring strength and hardness, and the mechanical properties and service life of the hardware shrapnel can be improved, while optimizing corrosion resistance and electrical properties.
[0026] Preferably, the specific steps of the surface treatment are: pickling, activating and nickel-plating the heat-treated sample in sequence.
[0027] Preferably, the specific step of pickling is: placing the sample in the pickling solution for 5 to 10 minutes.
[0028] Preferably, the pickling solution is sulfuric acid with a mass concentration of 10% to 15% or hydrochloric acid with a mass concentration of 5% to 10%.
[0029] Preferably, the specific step of the activation is: placing the sample in the activation solution for 5 to 10 minutes.
[0030] Preferably, the activation solution is a palladium chloride aqueous solution with a mass concentration of 0.1 to 0.2 g / L.
[0031] Preferably, the specific steps of nickel plating are: placing the sample in a plating solution, stirring the nickel plating for 30 to 60 minutes, washing the residual nickel plating on the surface with deionized water, and drying.
[0032] Preferably, the formula of the plating solution is: 20-30 g / L nickel sulfate, 20-30 g / L sodium hypophosphite, 10-20 g / L sodium citrate, 20-30 g / L boric acid, sodium acetate is used to adjust the pH value to 4.5-5.0, and the operating temperature is 80-90°C.
[0033] The inventors found that the use of a specific formula of plating solution to treat the initial sample after heat treatment can improve the corrosion resistance of the hardware shrapnel while also improving its contact stability and maintaining good electrical properties. This may be because nickel sulfate provides a nickel ion source, and sodium hypophosphite, as a reducing agent, reduces nickel ions to metallic nickel and deposits them on the surface of the substrate. The synergistic effect between the two ensures the formation and quality of the nickel plating layer; sodium citrate, as a chelating agent, forms a stable complex with nickel ions to prevent premature precipitation of nickel ions, which helps to maintain the stability of the plating solution and ensure the uniformity and smoothness of the plating layer; boric acid, as a buffer, maintains the pH value of the plating solution stable, further enhances the stability of the plating solution, and ensures the quality and uniformity of the plating layer. The synergistic effect of each component makes the plating layer uniform in thickness and fine in crystallization, which can protect the hardware shrapnel from corrosion and oxidation while maintaining its good electrical properties. At the same time, the coating has a good bonding force with the base metal, making the hardware shrapnel more stable and reliable when connected and contacted.
[0034] Preferably, the precision detection includes using high-precision detection equipment to perform size and shape tolerance detection on the manufactured hardware spring pieces to ensure that they meet the design requirements.
[0035] The second aspect of the present invention provides a hardware shrapnel prepared by the production process of the hardware shrapnel with stable contact performance.
[0036] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0037] 1. The present invention provides a hardware spring with stable contact performance. The corrosion resistance and contact performance of the hardware spring are improved by optimizing material selection, strengthening surface treatment and other measures. After millions of mechanical cycle tests, the hardware spring can still maintain excellent contact performance and stable electrical characteristics, thereby significantly improving the reliability and service life of the product.
[0038] 2. The present invention selects copper alloy as the raw material of the hardware spring piece and introduces metal elements Be, P, Sn and Zn in specific proportions, thereby improving the corrosion resistance of the hardware spring piece and improving its mechanical properties.
[0039] 3. The present invention can further improve various properties of the hardware spring piece by adding raw materials step by step for smelting and controlling the temperature.
[0040] 4. The present invention can eliminate internal stress and improve various properties of the hardware spring piece through a specific heat treatment step.
[0041] 5. The present invention uses a plating solution with a specific formula to treat the initial sample after heat treatment, which can improve the corrosion resistance of the hardware spring piece while also improving its contact stability and maintaining good electrical properties.
[0042] 6. The production process of the present invention is not only applicable to the manufacture of traditional hardware shrapnel, but can also be widely used in various shrapnel manufacturing fields that require high corrosion resistance and contact performance, and has broad market prospects and application value. DETAILED DESCRIPTION
[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Example 1
[0045] This embodiment provides a production process for a metal spring with stable contact performance, the steps of which are: S1, casting a raw material to obtain a preliminary sample;
[0046] S2. After the initial sample is subjected to heat treatment and surface treatment in sequence, it is subjected to precision testing and is considered qualified.
[0047] The raw material is a copper alloy, and its elemental composition is Be: 2%, P: 0.1%, Sn: 2%, Zn: 3% by weight, and the balance is Cu.
[0048] The specific steps of the casting molding are:
[0049] A1. Weigh copper ingots, tin ingots, zinc ingots, and Cu-P and Cu-Be master alloys according to the weight percentages of the elements of the raw materials;
[0050] A2, putting copper ingots, tin ingots, zinc ingots, and Cu-P and Cu-Be master alloys into an induction melting furnace, heating, stirring and keeping warm to obtain a melt;
[0051] A3, refining, degassing, and stirring the melt obtained in step A2, and then standing and keeping warm for 10 minutes;
[0052] A4. The melt obtained in step A3 is transferred to a preheated metal spring-shaped mold for cold stamping to obtain a preliminary sample.
[0053] The weight percentages of the metals in the Cu-P and Cu-Be master alloys are Cu-10P and Cu-2.0Be respectively.
[0054] The specific operation steps of step A2 are: preheating the smelting furnace to 450°C, adding copper ingots, heating to 1120°C, keeping the temperature for 20 minutes after complete melting, cooling to 1050°C, adding tin ingots and zinc ingots, keeping the temperature for 20 minutes after complete melting, cooling to 950°C, adding Cu-P master alloy, keeping the temperature for 20 minutes after complete melting, heating to 1150°C, adding Cu-Be master alloy, keeping the temperature for 20 minutes after complete melting, and obtaining a melt.
[0055] The specific conditions of the cold stamping forming are: the punching press tonnage is 100 tons and the stamping speed is 40 times / min.
[0056] The specific steps of the heat treatment are:
[0057] B1. Heat the initial sample to 200℃ and keep it for 8min, heat it to 450℃ and keep it for 8min, heat it to 650℃ and keep it for 40min, and cool it to room temperature with the furnace;
[0058] B2, heat the B1 sample to 850℃, keep it at that temperature for 40min, and then quickly cool it to room temperature;
[0059] B3. Heat the B2 sample to 380°C, keep it warm for 3 hours, and air cool it to room temperature.
[0060] The specific steps of the surface treatment are: pickling, activating and nickel-plating the heat-treated sample in sequence.
[0061] The specific steps of the pickling are: placing the sample in hydrochloric acid with a mass concentration of 8% for 8 minutes.
[0062] The specific steps of the activation are: placing the sample in a palladium chloride aqueous solution with a mass concentration of 0.15 g / L for 8 minutes.
[0063] The specific steps of nickel plating are: placing the sample in the plating solution, stirring the nickel plating for 40 minutes, washing the residual nickel plating on the surface with deionized water, and drying.
[0064] The formula of the plating solution is: 25 g / L nickel sulfate, 25 g / L sodium hypophosphite, 15 g / L sodium citrate, 25 g / L boric acid, sodium acetate is used to adjust the pH value to 4.5, and the operating temperature is 85°C.
[0065] Example 2
[0066] The difference between this embodiment and embodiment 1 is that the raw material is a copper alloy, and its elemental composition, by weight percentage, is Be: 2.5%, P: 0.1%, Sn: 2.5%, Zn: 2.5%, and the balance is Cu.
[0067] Example 3
[0068] The difference between this embodiment and embodiment 1 is that the formula of the plating solution is: 28 g / L nickel sulfate, 23 g / L sodium hypophosphite, 16 g / L sodium citrate, 27 g / L boric acid, sodium acetate is used to adjust the pH value to 4.5, and the operating temperature is 85°C.
[0069] Comparative Example 1
[0070] The difference between this comparative example and Example 1 is that the raw material is a copper alloy, and its elemental composition, by weight percentage, is Be: 2%, P: 0.1%, Sn: 2%, Zn: 6%, and the balance is Cu.
[0071] Comparative Example 2
[0072] The difference between this comparative example and Example 1 is that the raw material is a copper alloy, and its elemental composition, by weight percentage, is Be: 2%, P: 0.1%, Zn: 3%, and the balance is Cu.
[0073] Comparative Example 3
[0074] The difference between this comparative example and Example 1 is that the specific operation steps of step A2 are: preheating the smelting furnace to 400-500° C., adding raw materials, heating to 1100-1150° C., and keeping warm for 35-45 minutes after complete melting to obtain a melt.
[0075] Comparative Example 4
[0076] The difference between this comparative example and Example 1 is that the specific steps of the heat treatment are: heating the initial sample to 150-250°C and then keeping it warm for 5-10 minutes, heating it to 380-500°C and then keeping it warm for 5-10 minutes, heating it to 600-700°C and then keeping it warm for 30-60 minutes, and cooling it to room temperature with the furnace.
[0077] Comparative Example 5
[0078] The difference between this comparative example and Example 1 is that the specific steps of the heat treatment are:
[0079] B1. Heat the initial sample to 600-700℃, keep it warm for 30-60min, and then cool it to room temperature with the furnace;
[0080] B2, heat the B1 sample to 800-900°C, keep it warm for 30-60 minutes, and quickly cool it to room temperature;
[0081] B3. Heat the B2 sample to 300-450°C, keep it warm for 2-4 hours, and air cool it to room temperature.
[0082] Comparative Example 6
[0083] The difference between this comparative example and Example 1 is that the formula of the plating solution is: 25 g / L nickel sulfate, 25 g / L sodium hypophosphite, 25 g / L boric acid, the pH value is adjusted to 4.5 with sodium acetate, and the operating temperature is 85°C.
[0084] Comparative Example 7
[0085] The difference between this comparative example and Example 1 is that the formula of the plating solution is: 15 g / L nickel sulfate, 15 g / L sodium hypophosphite, 15 g / L sodium citrate, 25 g / L boric acid, sodium acetate is used to adjust the pH value to 4.5, and the operating temperature is 85°C.
[0086] Performance Testing
[0087] The prepared metal shrapnel was immersed in a 3.5% NaCl aqueous solution for seven days to test the corrosion rate. The contact resistance was measured using a contact resistance tester, and the contact resistance was required to be ≤10mΩ. A metal shrapnel keystroke life tester was used for mechanical cycle testing. The contact resistance after 1 million cycles of testing should not exceed 15mΩ. The results are shown in Table 1.
[0088] Table 1 Measurement results
[0089]
[0090] According to statistics, the metal shrapnel prepared by Examples 1 to 3 of the present invention has low corrosion rate and contact resistance. After 1 million mechanical cycles, the contact resistance is still maintained at about 10mΩ, indicating that the prepared metal shrapnel has excellent corrosion resistance, electrical properties and contact stability. In Comparative Example 1, Zn is added excessively, in Comparative Example 2, Sn is not added, in Comparative Example 3, step-by-step smelting is not performed, in Comparative Example 4, B2 and B3 heat treatment steps are missing, in Comparative Example 5, heat treatment step B1 is not subjected to step-by-step temperature increase treatment, in Comparative Example 6, sodium hypochlorite is not added, in Comparative Example 7, nickel sulfate and sodium hypophosphite are added in too little amount, and the prepared metal shrapnel has poor performance in all aspects. Therefore, the metal shrapnel prepared by the raw materials and methods described in this application has high corrosion resistance, excellent electrical properties and stable contact performance, thereby significantly improving the reliability and service life of the product.
[0091] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A production process for a metal spring with stable contact performance, characterized in that: The following steps are involved: S1, casting the raw materials to obtain a preliminary sample; S2. After the initial sample is subjected to heat treatment and surface treatment in sequence, it is subjected to precision testing, and the sample is obtained after it passes the test; The raw material is any one of stainless steel, copper, and copper alloy; The copper alloy, by weight percentage, has the following elemental components: Be: 0.5%-3%, P: 0.05%-0.2%, Sn: 1%-3%, Zn: 2%-4%, and the balance is Cu.
2. The production process of the metal spring with stable contact performance according to claim 1 is characterized in that: The specific steps of the casting molding are: A1. Weigh copper ingots, tin ingots, zinc ingots, and Cu-P and Cu-Be master alloys according to the weight percentages of the elements of the raw materials; A2, putting copper ingots, tin ingots, zinc ingots, and Cu-P and Cu-Be master alloys into an induction melting furnace, heating, stirring and keeping warm to obtain a melt; A3, refining, degassing, and stirring the melt obtained in step A2, and then standing and keeping warm for 8 to 12 minutes; A4. The melt obtained in step A3 is transferred to a preheated metal spring-shaped mold for cold stamping to obtain a preliminary sample.
3. The production process of the metal spring with stable contact performance according to claim 2 is characterized in that: The weight percentages of the metals in the Cu-P and Cu-Be master alloys are Cu-10P and Cu-2.0Be respectively.
4. The production process of the metal spring with stable contact performance according to claim 2 is characterized in that: The specific operation steps of step A2 are: preheating the smelting furnace to 400-500° C., adding copper ingots, heating to 1100-1150° C., keeping the temperature for 15-25 minutes after complete melting, cooling to 1000-1100° C., adding tin ingots and zinc ingots, keeping the temperature for 15-25 minutes after complete melting, cooling to 900-1000° C., adding Cu-P master alloy, keeping the temperature for 15-25 minutes after complete melting, heating to 1100-1200° C., adding Cu-Be master alloy, keeping the temperature for 15-25 minutes after complete melting, and obtaining a melt.
5. The production process of the metal spring with stable contact performance according to claim 1 is characterized in that: The specific steps of the heat treatment are: B1. Heat the initial sample to 150-250℃ and keep it warm for 5-10min, heat it to 380-500℃ and keep it warm for 5-10min, heat it to 600-700℃ and keep it warm for 30-60min, and cool it to room temperature with the furnace; B2, heat the B1 sample to 800-900°C, keep it warm for 30-60 minutes, and quickly cool it to room temperature; B3. Heat the B2 sample to 300-450°C, keep it warm for 2-4 hours, and air cool it to room temperature.
6. The production process of the metal spring with stable contact performance according to claim 1 is characterized in that: The specific steps of the surface treatment are: pickling, activating and nickel-plating the heat-treated sample in sequence.
7. The production process of the metal spring with stable contact performance according to claim 6 is characterized in that: The specific steps of nickel plating are: placing the sample in the plating solution, stirring the nickel plating for 30 to 60 minutes, washing the residual nickel plating on the surface with deionized water, and drying.
8. The production process of the metal spring with stable contact performance according to claim 7 is characterized in that: The formula of the plating solution is: 20-30 g / L nickel sulfate, 20-30 g / L sodium hypophosphite, 10-20 g / L sodium citrate, 20-30 g / L boric acid, sodium acetate is used to adjust the pH value to 4.5-5.0, and the operating temperature is 80-90°C.
9. The production process of a metal spring with stable contact performance according to claim 6, characterized in that: The specific steps of the activation are: placing the sample in the activation solution for 5 to 10 minutes; the activation solution is a palladium chloride aqueous solution with a mass concentration of 0.1 to 0.2 g / L.
10. A metal spring piece prepared according to the production process of a metal spring piece with stable contact performance according to any one of claims 1 to 9.
Citation Information
Patent Citations
Copper alloy contact line for electrified railways and preparation method of copper alloy contact line
CN103695698A
Method for preparing elastic brass alloy
CN104087783A
Chemical plating nickel-zinc-phosphorus alloy plating solution
CN106676503A
High load bearing shell made from beryllium-containing casting bronze
CN107663596A
Method of producing copper alloy sheet for high strength electrical / electronic component
JP2005163127A